KONTRIBUSI PERHATIAN ORANG TUA TERHADAP PENCAPAIAN AKADEMIK PAI SISWA KELAS XI SMAN 1 SABANG - Ilhamullah; Marzuki (Atta'dib Jurnal Pendidikan Agama Islam, 2025)
This study aims to determine the contribution of parental attention towards pai academic achievement of grade xi students of sman 1 sabang. Religious education, especially Islamic Religious Education (PAI), plays an important role in the formation of students' character and personality. However, parental attention to children's religious education is often less than optimal due to busyness, changes in lifestyle and the influence of technology. This study uses a quantitative approach with a descriptive correlational method. The sample of the study was 68 grade XI students of SMAN 1 Sabang, with a purposive sampling technique. Data were collected through a closed questionnaire and documentation of PAI subject PTS scores. The results showed that the contribution of parental attention had a positive and significant impact on PAI academic achievement of grade X1 students of SMAN 1 Sabang, with a correlation coefficient value of 0.768 and r table of 0.201. Ha was accepted and Ho was rejected, because r count > r table with a significant value of 0.000 < 0.05. Therefore, it can be concluded that the more attention parents give their children, the more positive the impact on their academic achievement in Islamic religious education. Conversely, the less parental attention a child receives, the lower their academic achievement in Islamic religious education.